Catalytic organometallic anticancer complexes - Dougan, Sarah J; Habtemariam, Abraha; McHale, Sarah E; Parsons, Simon; Sadler, Peter J (Proceedings of the National Academy of Sciences - PNAS, 2008)
Organometallic complexes offer chemistry that is not accessible to purely organic molecules and, hence, potentially new mechanisms of drug action. We show here that the presence of both an iodido ligand and a σ-donor/π-acceptor phenylazopyridine ligand confers remarkable inertness toward ligand substitution on the half-sandwich "piano-stool" ruthenium arene complexes [(η⁶-arene)Ru(azpy)I]⁺ (where arene = p-cymene or biphenyl, and azpy = N,N-dimethylphenyl- or hydroxyphenyl-azopyridine) in aqueous solution. Surprisingly, despite this inertness, these complexes are highly cytotoxic to human ovarian A2780 and human lung A549 cancer cells. Fluorescence-trapping experiments in A549 cells suggest that the cytotoxicity arises from an increase in reactive oxygen species. Redox activity of these azopyridine RuII complexes was confirmed by electrochemical measurements. The first one-electron reduction step (half-wave potential -0.2 to -0.4 V) is assignable to reduction of the azo group of the ligand. In contrast, the unbound azopyridine ligands are not readily reduced. Intriguingly the ruthenium complex acted as a catalyst in reactions with the tripeptide glutathione (γ-L-Glu-L-Cys-Gly), a strong reducing agent present in cells at millimolar concentrations; millimolar amounts of glutathione were oxidized to glutathione disulfide in the presence of micromolar ruthenium concentrations. A redox cycle involving glutathione attack on the azo bond of coordinated azopyridine is proposed. Such ligand-based redox reactions provide new concepts for the design of catalytic drugs.